Optimization of injection molding and solvent debinding parameters of stainless steel powder (SS316L) based feedstock for metal injection molding - Muhammad Ilman Hakimi Chua,; Abu Bakar Sulong,; Mohd Fazuri Abdullah,; Norhamidi Muhamad, (Universiti Kebangsaan Malaysia, 2013)
In this study, injection molding parameters, including green strength, surface quality and green part density, were optimized using the L18 Taguchi orthogonal array. The L25 Taguchi method was used to optimize the green density of solvent debinding parameters. The feedstock consisted of stainless steel powder (SS316L), with powder loading fractions of 63, 63.5 and 64 v/o. The binder compositions used in the study were polyethelene glycol (PEG-73 wt. %), polymethyl methacrilate (PMMA-25 wt. %) and stearic acid (2 wt. %). The Taguchi method was used to optimize the injection parameters. The obtained optimum parameters were as follows: mold temperature of 65oC, injection temperature of 145oC, injection pressure of 650 bar, injection flow rate of 20 m3/s, holding time of 5 s and powder loading of 64% v/o. Analysis of variance results showed that mold temperature has the greatest influence in the production of good green part surface quality and that powder loading gave the best green part strength. Immersion time and temperature were used to optimize for solvent debinding parameters. By optimizing the solvent debinding parameters, an immersion temperature of 61oC and immersion time of 5 h produced the highest density which is the optimum value gain in this study.